FAKTOR-FAKTOR YANG MEMPENGARUHI PARTISIPASI EKSPOR USAHA KECIL DI INDONESIA - ade mirdad (Fakultas Ekonomi Universitas Djuanda, 2026)
ABSTRACT This study examines the determinants of export participation among Indonesian SMEs using data from the World Bank Enterprise Surveys (WBES). A logistic regression (logit) model is employed, with export participation as a binary dependent variable (1 = exporter, 0 = non-exporter). The sample is restricted to small firms (5–19 employees) and medium firms (20–99 employees). The results show that digitalization (website ownership), process innovation, and managers’ experience have positive and significant effects on the probability of SMEs engaging in exports, with innovation being the strongest determinant. In contrast, formal worker training and firm age are found to have a significant negative relationship with export participation. Access to finance has a positive effect but is only significant at the 10% level, while transport obstacles show a positive association, indicating potential reverse causality as exporting firms may be more likely to report logistical constraints. These findings suggest that policies to promote SME exports in Indonesia should prioritize digital transformation, innovation support, and managerial capacity development, alongside improvements in training programs and logistics systems. ABSTRAK Penelitian ini menganalisis faktor-faktor yang memengaruhi partisipasi ekspor UMKM di Indonesia menggunakan data World Bank Enterprise Surveys (WBES). Metode yang digunakan adalah regresi logistik (logit) dengan variabel dependen berupa dummy ekspor (1 = eksportir, 0 = non-eksportir). Sampel dibatasi pada usaha kecil (5–19 tenaga kerja) dan menengah (20–99 tenaga kerja). Hasil estimasi menunjukkan bahwa digitalisasi (kepemilikan website), inovasi proses, dan pengalaman manajer berpengaruh positif dan signifikan terhadap probabilitas UMKM menjadi eksportir, dengan inovasi sebagai determinan terkuat. Sebaliknya, pelatihan formal tenaga kerja dan umur usaha berpengaruh negatif signifikan terhadap partisipasi ekspor. Akses pembiayaan berpengaruh positif namun hanya signifikan pada tingkat 10%, sedangkan hambatan transportasi menunjukkan hubungan positif yang mengindikasikan potensi reverse causality. Temuan ini menegaskan bahwa kebijakan peningkatan ekspor UMKM perlu difokuskan pada penguatan digitalisasi, inovasi, dan kapasitas manajerial, disertai perbaikan program pelatihan serta sistem logistik.